Evidence for two stages of mineralization in West Africa's largest gold deposit: Obuasi, Ghana - Fougerouse, Denis; Micklethwaite, S.; Ulrich, S.; Miller, J.; Godel, B.; Adams, D.; McCuaig, T. (Society of Economic Geologists Inc, 2017)
The supergiant Obuasi gold deposit is the largest deposit in the Paleoproterozoic Birimian terranes of West Africa with 62 Moz of gold (past production + resources). The deposit is hosted in the Paleoproterozoic Kumasi Group sedimentary rocks composed of carbonaceous phyllites, slates, psammites, and volcaniclastic rocks intruded by different generations of felsic dikes and granites. A three-stage deformation history is defined for the district. The D1Ob stage is weakly recorded in the sedimentary rocks as a layer-parallel fabric and indicates that bedding parallel shearing occurred during the early stage of deformation at Obuasi. The D2Ob is the main deformation stage affecting the Obuasi district and corresponds to a NW-SE shortening. Tight to isoclinal folding, as well as intense subhorizontal stretching, occurred during D2Ob, parallel with the plane of a pervasive NE-striking subvertical foliation (S2Ob). Finally, a N-S shortening event (D3Ob) refolded previously formed structures and formed a distinct ENE-striking, variably dipping S3Ob cleavage that is domainal in nature throughout the deposit. Two economic styles of mineralization occur at Obuasi and contribute equally to the gold budget. These are (1) gold-bearing sulfides, dominantly arsenopyrite, mainly disseminated in metasedimentary rocks and (2) native gold hosted in quartz veins that are as much as 25 m wide. Microstructural evidence, such as strain shadows surrounding gold-bearing arsenopyrite parallel with S2Ob, but folded by S3Ob, indicates that the sulfides were formed during D2Ob. Concentrations of as much as 700 ppm Au are present in the epitaxial growth zones of the arsenopyrite grains. Although the large mineralized quartz veins are boudinaged and refolded (indicating their formation during D2Ob), field and microanalytical observations demonstrate that the gold in the veins is hosted in microcracks controlled by D3Ob, where the S3Ob cleavage crosscuts the quartz veins in the main ore zones. Thus, these observations constitute the first evidence for multiple stages of gold deposition at the Obuasi deposit. Futhermore, three-dimensional modeling of stratigraphy, structure, and gold orebodies highlights three major controls on oreshoot location, which are (1) contacts between volcaniclastic units and pre-D1 felsic dikes, (2) fault intersections, and (3) F3Ob fold hinges. The maximum age for the older disseminated gold event is given by the age of the granites at 2105 ± 2 Ma, which is within error of hydrothermal rutile in the granites of 2098 ± 7 Ma; the absolute age of the younger gold event is not known.